Effect on the Volume of Solvents after Dissolution of Solution - Parashar, Renu; Parashar, R.K. (SCHOOL SCIENCE, 2017)
The present paper deals with the change in volume of the solvent when a solid solute is dissolved into it. The results are presented with respect to the change of volume of solvent, the total volume of solvent and solute, and in terms of the molar concentration of solutions. Keywords: Solute, solvent. Solution, solvation, volume change, molar concentration